Tumor necrosis factor α1 (TNFα1) administration can disrupt barrier function and attenuate redox defense in midgut of red crucian carp (Carassius auratus red var) - Huang, Jin-Fang; Xiong, Ning-Xia; Li, Shi-Yun; Li, Ke-Xin; Ou, Jie; Wang, Fei; Luo, Sheng-Wei (Reproduction and breeding, 2023)
TNFα belongs to superfamily of tumor necrosis factor that can exert the pleiotropic effort in a large quantity of biological processes, including immune homeostasis, intracellular modulation and etiopathogenesis, but its regulatory role in mucosal immune regulation of fish is unclear. Currently, this study aimed to evaluate the immunoregulatory function of TNFα1 on gut barrier in teleost fish. In this study, TNFα1 sequences were identified from red crucian carp (RCC, Carassius auratus red var). The high-level expression of RCC-TNFα1 mRNA was detected in gill among all the isolated samples. Then, RCC-TNFα1 expression increased dramatically in immune-related tissues after A. hydrophila infection and in cultured fish cells after lipopolysaccharide (LPS) treatment. RCC-TNFα1 fusion protein was generated and purified in vitro. RCC receiving RCC-TNFα1 perfusion showed an increased levels of villi fusion and edema in injured midgut with the fuzzy appearance. In addition, The mRNA expressions of tight junction (TJ) genes, mucin genes and redox sensitive genes decreased sharply in TNFα1-treated midgut in comparison with those of the control (P < 0.05), whereas the expression levels of apoptotic genes involved in caspase signals and unfolded protein response (UPR) attained the dramatic increase. These results demonstrated that RCC-TNFα1 stimulation could impair midgut structural integrity and immune function by induction of antioxidant collapse and apoptotic activation.